Two-dimensional Mo(SCN)2: a novel MoS2-variant. (6th January 2017) - Kaltsas, Dimitrios; Tsetseris, Leonidas
Abstract: Transition metal dichalcogenides (TMDC) are currently among the most studied two-dimensional (2D) materials. Based on first-principles calculations we propose a new family of 2D materials which resemble TMDC's, but contain more complex chemical groups instead of elemental chalcogen atoms. In particular, we identify various stable 2D polymorphs of molybdenum di-thiocyanate, Mo(SCN)2, with structures akin to those of MoS2 . The most stable Mo(SCN)2 polymorphs are semiconductors with small energy band gaps, whereas a higher-energy structure is metallic. Since the calculated formation energies of MoS2 and Mo(SCN)2 are comparable, the synthesis of the latter should be feasible.